Nomenclature and Identity of some Bamboo Species - Naithani, H. B. (Indian Forester, 1999)
Earlier due to non-availability of sufficient material for correct identity some Bamboo species were creating nomenclatural problems. The present paper is an attempt to rectify the confusion as follows: (i) Bambusa auriculata Kurz flowered in Calcutta Botanic Garden in January 1898. A critical examination of its culm sheath and flowers it was found conspecific to Gigantochloa andamanica (Kurz) Kurz. (ii) Gigantochloa microstachya. Kurz is a mixture of two different species, its culm sheath belong to Bambusa tulda and its allies, while inflorescence is of proper G. macrostachya. Culm sheath sensu Gamble (1896) kept under Bambusa affinis non Munro now belong to G. macrostachya. Gigantochloa rostrata Wong a Malayan species also identical to G. macrostachya which is at present merged under G. macrostachya. Present studies indicate that G. macrostachya is so far known only from Myanmar and Malaya. (iii)Dinochloa maclellandii growing in the Arboretum of Forest Research institute Dehra Dun. Its vegetative parts, flowers and fruits were studied and found them identical to genus Melocalamus. Thus a new combination viz. Melocalamus maclellandii(Munro) Naithani has been proposed.